Ribosomal Protein L23 Drives the Metastasis of Hepatocellular Carcinoma via Upregulating MMP9 - Yang, Minli; Zhou, Yujiao; Deng, Haijun; Zhou, Hongzhong; Cheng, Shengtao; Zhang, Dapeng; He, Xin; Mai, Li; Chen, Yao; Chen, Juan (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths globally. Tumor metastasis is one of the major causes of high mortality of HCC. Identifying underlying key factors contributing to invasion and metastasis is critical to understand the molecular mechanisms of HCC metastasis. Here, we identified RNA binding protein L23 (RPL23) as a tumor metastasis driver in HCC. RPL23 was significantly upregulated in HCC tissues compared to adjacent normal tissues, and closely related to poor clinical outcomes in HCC patients. RPL23 depletion inhibited HCC cell proliferation, migration and invasion, and distant metastasis. Mechanistically, RPL23 directly associated with 3’UTR of MMP9, therefore positively regulated MMP9 expression. In conclusion, we identified that RPL23 might play an important role in HCC metastasis in an MMP9-dependent manner and be a potential therapeutic target for HCC tumorigenesis and metastasis.